2021
DOI: 10.1007/s11926-021-01039-1
|View full text |Cite
|
Sign up to set email alerts
|

Enthesitis in Psoriatic Arthritis, the Sonographic Perspective

Abstract: Purpose of Review To provide an overview of the ultrasound (US) studies focusing on enthesitis in psoriatic arthritis (PsA). Recent Findings Last-generation US equipment has demonstrated the ability to detect subtle morphostructural and vascular abnormalities at entheseal level. US is able to identify pathologic changes in both “classical” (i.e., the site of attachment of tendons, ligaments, and joint capsules into the bone) and “functional” enthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 76 publications
1
7
0
1
Order By: Relevance
“…The poor inter-observer reliability in clinical identification of enthesitis and lack of precision in its diagnosis justify the need for alternative imaging modalities, such as magnetic resonance imaging and US. US has many practical ad-vantages over magnetic resonance imaging, such as low cost, ease of access to multiple anatomical sites, and higher sensitivity and specificity for peripheral entheses lesions 24,25 . We evaluated the role of US in the diagnosis of subclinical enthesitis in patients with PsO, factors affecting enthesitis, and progression of enthesitis in patients with PsO at 1-year follow-up, using MASEI scoring.…”
Section: Discussionmentioning
confidence: 99%
“…The poor inter-observer reliability in clinical identification of enthesitis and lack of precision in its diagnosis justify the need for alternative imaging modalities, such as magnetic resonance imaging and US. US has many practical ad-vantages over magnetic resonance imaging, such as low cost, ease of access to multiple anatomical sites, and higher sensitivity and specificity for peripheral entheses lesions 24,25 . We evaluated the role of US in the diagnosis of subclinical enthesitis in patients with PsO, factors affecting enthesitis, and progression of enthesitis in patients with PsO at 1-year follow-up, using MASEI scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Скованность и ограничение подвижности в суставах отмечались у 27,5 и 26,2% больных псориазом соответственно (по сравнению с 80,0 и 71,2% больных ПА, р < 0,001), у части больных обеих групп встречались боли в спине (у 7,5% больных псориазом и 30,0% больных ПА, р < 0,001), однако большая часть больных в группе псориаза не предъявляла никаких жалоб (65,0% против 0% в группе сравнения, р < 0,001 нагрузка, соответственно, на крупные суставы (у 45,0 и 61,2% больных, р = 0,040) и суставы позвоночника (у 15,0 и 35,0% больных, р = 0,004). По данным разных авторов, поражение связочного аппарата при ПА выявляется раньше, чем воспаление суставных поверхностей, и связано с высокими функциональными нагрузками определенных сухожилий и энтезисов [18,19]. В нашем исследовании при сопоставлении анамнестических данных с наличием изоморфной реакции клинические признаки воспаления сухожилий и энтезисов в сочетании с соответствующим анамнезом были обнаружены у 47,5% в группе больных псориазом и 68,7% в группе больных ПА (р = 0,007), при этом преобладающим признаком оказался тендинит кистей при пальпации (у 40,0 и 63,7% соответственно, р = 0,003%).…”
Section: Discussionunclassified
“…[ 23 ] Ultrasound can be used to visualize morphostructural and vascular abnormalities indicative of entheseal inflammation, and it has been proven to be reliable for the evaluation of peripheral entheses in PsA. [ 24 ] Conversely, MRI allows for a comprehensive assessment of enthesitis at both peripheral and axial levels. Guo et al [ 25 ] found that enthesitis was more commonly detected by whole-body MRI than by clinical assessment in patients with spondyloarthritis.…”
Section: Discussionmentioning
confidence: 99%